Dialogue : techniques and exercises for crafting effective dialogue - Kempton, Gloria, 1951- (Cincinnati, OH : Writer's Digest Books, 2004)
Offers fiction writers tips on how to create believable dialogue, with interactive exercises and expert advice.
Includes index.
Adult
Keywords: Dialogue; Fiction -- Technique; Dialogue; Fiction -- Technique